Are we one? : Jewish identity in the United States and Israel - Auerbach, Jerold S. (Rutgers University Press, 2001)
"What binds together Jews of Israel and the United States? Amid the hope and frustration generated by the Middle East peace process, the meaning of Jewish state-hood is more vigorously contested than ever before. A secular democratic Israel, responsive to Western liberal values, is prepared to make peace with the Palestinians by sacrificing its own historic homeland. But a covenantal Israel, which draws its Jewish identity from divine promise and the biblical narrative, refuses to surrender to modern imperatives. As the very nature of Jewish statehood has become ever more polarized, American Jewish life has been profoundly affected by this fateful Zionist contradiction."